Analysis The Effect of Open Unemployment, Labor Force Participation and Human Development Index on Economic Growth - Ragil Andrean; I Ketut Patra; Rahmad Solling Hamid (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2025)
As one of the main benchmarks, economic growth does not only focus on production figures alone, but must also be seen in the context of equitable distribution of development results. The high Open Unemployment, the low Labor Force Participation, and the low Human Development Index in South Sulawesi are issues that need further research. This study aims to analyze the effect of Open Unemployment, Labor Force Participation, and Human Development Index on economic growth in South Sulawesi. This research uses quantitative methods with panel data covering 24 districts/cities in South Sulawesi during the period 2010-2023. Data were obtained from various official sources such as the Central Bureau of Statistics (BPS) of South Sulawesi Province, the Manpower Office, and other relevant government agencies. The data analysis technique used was multiple linear regression. The results showed that the Open Unemployment had no significant effect on economic growth. Similarly, the Labor Force Participation did not show a significant effect. However, the Human Development Index has a significant effect on economic growth. Simultaneously, these three variables have a significant effect on economic growth with an Adjusted R Square value of 0.979. The results of this study emphasize the importance of improving the quality of the workforce, reducing the unemployment, and investing in the education and health sectors to promote inclusive and sustainable economic growth.Keywords: Open Unemployment, Labor Force Participation, Human Development Index, Economic Growth.